Comparing ICH-Leach and Leach descendents on Image Transfer using DCT - Bennani Taj; Mhamed Ait Kbir (Institute of Advanced Engineering and Science, 2018)
The development and miniaturization of CMOS (microphones and cameras) in the last years have allowed the creation of WMSN (Wireless Multimedia Sensor Network). Therefore, transferring multimedia content through the network has become an important field of research. It transmits the recorded multimedia data wirelessly from a node to another to reach the Sink (base station). Thus, routing protocols make a big contribution in this process, because they participate in optimizing the node's resource usage. Since Leach protocol was designed only to minimize energy consumption of the network .The goal of this paper is to compare our protocol in tnansfering images with other Leach protocol descendants .By using the application layer, we applied the jpeg compression using the frequency domain on images before sending them to the network.In this paper ,readers will find statistics concerning the lifetime of the network , the energy consumption and most importantly statistics about received images .Also, we used Castalia framework to simulate real conditions of transmission .simulation results proved the efficiency of our protocol by prolonging the lifetime of the network and transmitting more images with better quality compared to other protocols.